Use of mesenchymal stem cells seeded on the scaffold in articular cartilage repair - Kaoru Yamagata; Shingo Nakayamada; Yoshiya Tanaka (BMC, 2018)
Abstract Articular cartilage has poor capacity for repair. Once damaged, they degenerate, causing functional impairment of joints. Allogeneic cartilage transplantation has been performed for functional recovery of articular cartilage. However, there is only a limited amount of articular cartilage available for transplantation. Mesenchymal stem cells (MSCs) could be potentially suitable for local implantation. MSCs can differentiate into chondrocytes. Several studies have demonstrated the therapeutic potential of MSCs in the repair of articular cartilage in animal models of articular cartilage damage and in patients with damaged articular cartilage. To boost post-implantation MSC differentiation into chondrocytes, the alternative delivery methods by scaffolds, using hyaluronic acid (HA) or poly-lactic-co-glycolic-acid (PLGA), have developed. In this review, we report recent data on the repair of articular cartilage and discuss future developments.